2014
DOI: 10.1080/03014223.2014.936881
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring ungulates in steep non-forest habitat: a comparison of faecal pellet and helicopter counts

Abstract: Faecal pellet counts have been widely used to monitor the abundances of introduced ungulates in New Zealand, but ground-based sampling cannot be conducted safely in the steep non-forest habitats that are common in New Zealand's Southern Alps. Helicopter counts may be an effective technique for monitoring ungulates in steep non-forest habitat. We evaluated the relationship between faecal pellet and helicopter counts of ungulates (primarily feral goat Capra hircus) at 12 non-forest sites in the Southern Alps. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In steep or otherwise dangerous terrain, not all quadrats on a transect can be sampled; for those quadrats, the FPI is calculated by dividing the total number of intact pellets by the number of quadrats sampled and then multiplying by 30. Forsyth et al (2007) showed a positive and approximately linear relationship between FPI and known deer density in 20 enclosures throughout New Zealand, and a subsequent study showed a positive curvilinear relationship between helicopter counts of ungulates (primarily feral goat) and FPI (Forsyth et al 2014). It is therefore reasonable to infer that higher faecal pellet abundances indicate higher ungulate abundances.…”
Section: Design Of the Ungulate Monitoring Within Doc's Biodiversity mentioning
confidence: 92%
See 1 more Smart Citation
“…In steep or otherwise dangerous terrain, not all quadrats on a transect can be sampled; for those quadrats, the FPI is calculated by dividing the total number of intact pellets by the number of quadrats sampled and then multiplying by 30. Forsyth et al (2007) showed a positive and approximately linear relationship between FPI and known deer density in 20 enclosures throughout New Zealand, and a subsequent study showed a positive curvilinear relationship between helicopter counts of ungulates (primarily feral goat) and FPI (Forsyth et al 2014). It is therefore reasonable to infer that higher faecal pellet abundances indicate higher ungulate abundances.…”
Section: Design Of the Ungulate Monitoring Within Doc's Biodiversity mentioning
confidence: 92%
“…We therefore conducted an additional analysis of sites in each of the North and South Islands where red deer rather than other ungulates are likely to be numerically dominant. In particular, feral goat (North and South Islands) and Himalayan tahr (South Island) have either excluded red deer and/or commonly attained much higher densities than red deer in recent decades (Forsyth and Hickling 1998;Forsyth et al 2014;Parkes 2021), and hence they could potentially obscure significant impacts of WAROs on red deer occupancyabundance. We therefore used the current ungulate distribution GIS layers (Department of Conservation 2014) to identify the North Island and South Island sites with red deer but not feral goat or Himalayan tahr.…”
Section: Analysesmentioning
confidence: 99%
“…The main prey of wolves in Valais are forest-dwelling, fairly elusive animals (Coppes, Burghardt, Hagen, Suchant, & Braunisch, 2017) whose abundance is difficult to estimate. Conventional survey methods of ungulates include direct visual counts, scat and track counts, trail camera trapping and genetic sampling (Ebert, Sandrini, Spielberger, Thiele, & Hohmann, 2012;Forsyth, MacKenzie, & Wright, 2014;Singh & Milner-Gulland, 2011). Widely deployed, they concern mostly monitoring for estimating population trends (Singh & Milner-Gulland, 2011).…”
Section: Estimating Prey Abundance Under Imperfect Detectionmentioning
confidence: 99%
“…Feral goat detectability ( d h ) using the helicopter survey technique was estimated from the number of known Judas individuals or particular feral goat individuals detected within a MU during a survey, and the number known (expected) to exist. The probability of detection is known to vary according to a range of factors including tree cover and terrain steepness (Bayne et al 2000; Forsyth et al 2014) but these aspects were not assessed during the helicopter surveys on KI.…”
Section: Methodsmentioning
confidence: 99%